On the Role of Adenosine A2A Receptor Gene Transcriptional Regulation in Parkinson’s Disease - Falconi, Anastasia; Bonito-Oliva, Alessandra; Di Bartolomeo, Martina; Massimini, Marcella; Fattapposta, Francesco; Locuratolo, Nicoletta; Dainese, Enrico; Pascale, Esterina; Fisone, Gilberto; D’Addario, Claudio (Frontiers in Neuroscience, 2019)
Adenosine A2A receptors (A2ARs) have attracted considerable attention as an important molecular target for the design of Parkinson’s disease (PD) therapeutic compounds. Here, we studied the transcriptional regulation of the A2AR gene in human peripheral blood mononuclear cells (PBMCs) obtained from PD patients and in the striatum of the well-validated, 6-hydroxydopamine (6-OHDA)-induced PD mouse model. We report an increase in A2AR mRNA expression and protein levels in both human cells and mice striata, and in the latter we could also observe a consistent reduction in DNA methylation at gene promoter and an increase in histone H3 acetylation at lysine 9. Of particular relevance in clinical samples, we also observed higher levels in the receptor gene expression in younger subjects, as well as in those with less years from disease onset and less severe disease according to clinical scores. In conclusion, the present findings provide further evidence of the relevant role of A2AR in PD and, based on the clinical data, highlight its potential role as disease biomarker for PD especially at the initial stages of disease development. Furthermore, our preclinical results also suggest selective epigenetic mechanisms targeting gene promoter as tool for the development of new treatments.